Creation of an Anti-Inflammatory, Leptin-Dependent Anti-Obesity Celastrol Mimic with Better Druggability - Zhou, Bo; Yuan, Yaxia; Shi, Le; Hu, Sheng; Wang, Dong; Yang, Yang; Pan, Yuanhu; Kong, Dexin; Shikov, Alexander N.; Duez, Pierre; Jin, Moonsoo; Li, Xiaohua; et al. (Frontiers in Pharmacology, 2021)
Obesity is characterized by an excessive body mass, but is also closely associated with metabolic syndrome. And, so far, only limited pharmacological treatments are available for obesity management. Celastrol, a pentacyclic triterpenoid from a traditional Chinese medicine (Tripterygii wilfordii Hook.f.), has shown remarkable potency against obesity, inflammation and cancer, but its high toxicity, low natural abundance and tedious chemical synthesis hindered its translation into clinics. In the present work, a triterpenoid library was screened for compounds with both high natural abundance and structural similarity to celastrol; from this library, glycyrrhetinic acid (GA), a compound present in extremely high yields in Glycyrrhiza uralensis Fisch. ex DC., was selected as a possible scaffold for a celastrol mimic active against obesity. A simple chemical modification of GA resulted in GA-02, a derivative that suppressed 68 % of food intake in diet-induced obesity mice and led to 26.4 % weight loss in two weeks. GA-02 plays a role in obesity treatment by re-activating leptin signaling and reducing systemic and, more importantly, hypothalamic inflammation. GA-02 was readily bioavailable with unnoticeable in vitro and in vivo toxicities. The strategy of scaffold search and modification on the basis of bio-content and structural similarity has proved to be a green, economic, efficient and practical way of widening the medicinal applications of "imperfect" bioactive natural compounds.